Cardboarding mixed reality with Dürer Machines - Araújo, António (2018)
Mixed reality is a direct application of 15 to 17th century principles of anamorphosis. The inherent physicality of anamorphosis, materialized through the Dürer perspective machine makes it an excellent teaching tool for students of digital art interested in mixed reality, whose initial core competencies may be extremely varied. The needs of these students are not met by the mere ephemera of learning how to use a particular piece of software; such knowledge is both transient and limiting of imaginative possibilities. We discuss a didactic strategy of cardboarding, i.e., a process of deliberate rudimentarization, to expose the inner workings of opaque chains of digital processes, to both clarify the elements of these chains and create loci for artistic intervention at their points of connection.